2018
DOI: 10.1158/1055-9965.epi-18-0121
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Elevations in TNFα and IL6 in the Human Colon and Procancerous Changes in the Mucosal Transcriptome Accompany Adiposity

Abstract: Background: Obesity, a risk factor for colorectal cancer, raises systemic levels of proinflammatory mediators. Whether increased levels also reside in the colons of obese individuals and are accompanied by procancerous alterations in the mucosal transcriptome is unknown.Methods: Concentrations of TNFa, IL1b, and IL6 in blood and colonic mucosa of 16 lean and 26 obese individuals were examined. Differences in the mucosal transcriptome between the two groups were defined.Results: Plasma IL6 and TNFa were 1.4-to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…For instance, TNF-α has been found in both acute and chronic inflammatory states, where it seems to promote and amplify IR by inhibiting INSR signaling [ 170 , 171 ]. In addition, higher levels of circulating TNF-α have been associated with tumorigenesis in overweight IR patients, in which its anti-apoptotic effect was most likely due to the activation of the NFκB pathway [ 172 ].…”
Section: Adipose Tissue Obesity Inflammation and Cancermentioning
confidence: 99%
“…For instance, TNF-α has been found in both acute and chronic inflammatory states, where it seems to promote and amplify IR by inhibiting INSR signaling [ 170 , 171 ]. In addition, higher levels of circulating TNF-α have been associated with tumorigenesis in overweight IR patients, in which its anti-apoptotic effect was most likely due to the activation of the NFκB pathway [ 172 ].…”
Section: Adipose Tissue Obesity Inflammation and Cancermentioning
confidence: 99%
“…Further, a number of studies in animal models and in human colonocytes have demonstrated the causal roles that cytokines such as TNF‐α and IL‐1β play in promoting carcinogenesis. Importantly, animal and humans studies alike have shown that obesity not only increases the concentration of circulating inflammatory cytokines, but also increases IL‐6 and TNF‐α in the colonic mucosa . IL‐6, in particular, is highly up‐regulated in colorectal neoplasms and considered to be instrumentally important during tumorigenesis and metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon exists in the colons of obese rodents and humans as well: rodent models have demonstrated that obesity and/or a high‐fat diet (HFD) increases the colonic concentrations of IL‐1β, IL‐6, and TNF‐α, possibly via the TLR4 signaling pathway . Similarly, colonic IL‐6 and TNF‐α have been shown to increase incrementally with BMI in human subjects, achieving concentrations two‐ to threefold among those whose BMI is ≥34 compared to those whose BMI is 18–25 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the mediator for inflammation are cytokines and inflammation-related molecules (Hursting et al, 2012). A study reported that increased body mass index (BMI) was associated with increase in two proinflammatory colonic cytokines, namely TNF-a and interleukin 6 (IL6), while obesity coincided with precancerous changes in the transcriptome (Pfalzer et al, 2018). Considering the existing correlation between obesity and gut microbiota changes (Boulangéet al, 2016), finding from Pfalzer et al (2018) implies that inflammation may be one of the mechanisms of how obesityassociated dysbiosis contributes to increased CRC risk.…”
Section: The Underlying Molecular Mechanisms Of Colon Carcinogenesis mentioning
confidence: 99%